THE HISTORICAL FOUNDER OF MODERN PSYCHOTHERAPY (Proceedings of International Educators Conference, 2024)
In this article, the psychotherapeutic methods studied and put into practice by psychologists of the present time and the unknown author who created a rare work as their founder are mentioned. The peculiarities of his work are important as the historical roots of modern psychology, the psychological pathology, its types and remedies are revealed in it.